IDENTIFIKASI KESULITAN SISWA SMP KELAS VII DALAM MENYELESAIKAN BUTIR SOAL PADA MATERI HIMPUNAN - Eki Rizki Mustari (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
This study aims to determine the results of the identification of student difficulties in solving set items, using descriptive research methods that emphasize factual findings in the field with the subject of 20 students of SMP class VII in Cimahi. The data collection technique is based on written tests and direct interviews with 5 items as instruments based on predetermined indicators. An analysis of 3 types of difficulty aspects is carried out including: 1).Language, 2). Prerequisites and 3). Applied. Based on the results of the identification, it shows that the achievement of students in solving problems is 80% and some students have difficulty on the 5th item which is categorized as difficult.